Accessibilities, Social Participation and Support for Students of The TU Students with Disabilities Program - นรามาศ กิตติยา; รุ่งฤกษ์ฤทธิ์ ชไมพร; โคตรบึงแก วิไลภรณ์ (Journal of Social Work and Social Administration, 2019)
Thammasat University Students with Disabilities Program which has begun since 2003 reflecting Thammasat University’s grounding principle “Thammasat For the People”. The Program has developed at the policy and practical levels which is consequently recognized by Universal Design and Friendly Design Building Awards. The present study is aimed at 1) to explore the accessibility of supports and buildings 2) to study participation of students with disabilities in various activities and 3) to study support services and good practice of Thammasat University Students with Disabilities Program. Findings revealed that students with disabilities are mostly positive about accessibility and participation in activities, very satisfied with accessibility to Disability Students Service Center-DSS, moderately satisfied with academic advisor system, and less satisfied with a peer support system. Important recommendations are DSS should be proactive and create social space which allows students with and without disabilities to be involved in activities. Activities that students with disabilities can contribute to society should be encouraged. There should be a central academic advisor and the available student database should be available for future job matching.